PENGARUH PENGENDALIAN INTERN, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KUALITAS SUMBER DAYA MANUSIA TERHADAP KETERANDALAN PELAPORAN KEUANGAN DAERAH (Studi Pada Satuan Kerja Perangkat Daerah Kota Payakumbuh) - Aini, Fitratul; Tanjung, Amries Rusli; Anggraini, Lila (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to examine the influence of the internal control, information technology utilization, and quality of human resources on the local government financial reporting reability. This study was conducted at SKPD of Payakumbuh city. The population in this study were employed who worked in the SKPD Payakumbuh city (25 government agencies). The sampling method used in this study is purposive sampling method. The respondent in this study is the head of SKPD, the head of financial, treasurer of SKPD and financial staff is a side direct related in the financial management area on government of Payakumbuh city. The sample used in this study were 75 respondents. The hypotheses then tested is multiple linear regression analysis by using SPSS version 20.0.The result of this study indicated that internal control and quality of human resources tend to have effect on local government financial reporting reability. While information technology utilization has no effect on local govermeny financial reporting reability. The magnitude of the effect (R2) internal control, information technology utilization and quality of human resources on the local government financial reporting reability was 35,9%. While the remaining 64,1% is influenced by other independent variabel that are not observed in this study.Keywords: Reporting, Control, Information Technology, and Human Resources.